Intolerância à lactose e o manejo dos sintomas com probióticos e prebióticos: uma revisão sistemática - Oliveira, Luiza Scalcon de (2022)
Lactose intolerance (IL) is characterized by the decrease or inability to digest lactose, therefore some symptoms such as diarrhea, flatulence, abdominal distension, among others, may appear. The appearance of IL symptoms is multifactorial, depending on the amount of lactose that the individual ingested and the amount of lactase that the body produces. The treatment of IL initially consists of removing the sources of lactose, followed by the gradual reintroduction of dairy products, following the individual's tolerance. Enzyme replacement is also a procedure used to improve symptoms. Approaches using probiotics and/or prebiotics have been evaluated to help manage the condition. Probiotics are beneficial microorganisms that can provide improved health through the balance of the gastrointestinal microbiota. Prebiotics are oligosaccharides that stimulate the growth and/or activity of a group of microorganisms in the gastrointestinal tract, promoting benefits to the health of the individual. The presence of this microbiota favors the metabolism of lactose, providing improvement in the symptoms of IL. Despite the existence of data involving IL and the use of probiotics or prebiotics, it is difficult to find in the literature, specifically, studies that reassess the symptoms of IL with products containing lactose at the end of the use of microorganisms and/or oligosaccharides. Therefore, the present research aims to investigate, through a systematic review, the efficiency of the clinical application of probiotic and prebiotic supplements in reducing the symptoms of IL, in order to gather useful evidence for health professionals in the recommendation and management of symptoms. in people with IL. The PRISMA 2020 guidelines were used to carry out the research. The studies were retrieved from the following databases: SciElo, PubMed, LILACS, ScienceDirect, and the gray literature. For the risk of bias, the RoB 2.0 tool was adopted, and for the certainty analysis of the findings, the GRADE tool was used. A total of 830 studies were found, 5 were included in this review, and the others did not meet the inclusion criteria. Two studies addressed a prebiotic and three studies addressed several probiotics. The probiotics Lactobacillus reuteri and the DDS-1 of Lactobacillus acidophilus, and the prebiotics GOS RP-G28, stood out. Post-treatment, the prebiotic appeared to be more effective in reducing symptoms. The risk of bias for studies on probiotics presented concerns in all studies evaluated, whereas for prebiotics only one of the studies presented any concerns. The certainty of evidence was high for the prebiotic GOS RP-G28, on the other hand, it was low for the probiotics due to methodological biases and the low number of individuals included. It is known that food is not used as a treatment, however, this RS presents an alternative approach to help reduce IL symptoms. Among the limitations, heterogeneity and lack of data made it impossible to carry out a sensitivity analysis. Evidence for functional claims for probiotics has been shown to be very low, and for prebiotics data are limited. New studies are needed, adopting robust methodologies, especially in the full disclosure of data.